PERAN SEMAR DALAM PERTUNJUKAN WAYANG KULIT JAWA GAYA SURAKARTA (Harmonia: Journal of Arts Research and Education, 2009)
Semar is the mysterious puppet charaters and vague. Semar is present in all versions ofleather puppet theater performances. Stories in puppet shows, Semar is present in twomain roles, first as a supporter of the birth of the holder of the most important role in theplay, namely the presence of seeds that will take a decisive position in the theater, precededby his presence because, seond Semar become major stakeholders in play as an example:Kilat Buana, Semar Kuning, Semar Papa, Semar Mbarang Jantur. Semar represent sudrafigures, also represent the people in general. In the play lebet containing about philosophyof life, the presence of Semar preceded by events because it is an extraordinary event. Garagarain the puppet shows are usually marked by a major event in the universe caused by avariety of puppet characters. It appeared to subside after Semar figure. As the atmosphereConditioning, Semar comes with poise, dignity many illustrations that can be interpretedfrom him. Semar restore the harmony of the play that ended mulih play according to plan.Things returned to normal play Semar sometimes even appear as a fresh air carriers and thehumorous seasoning with punakawan others, can be used to establish rapport with theaudience. Semar is a symbol characters will be elected to the presence of a knight, who has agenuine spirit of struggle, and the birth of world harmony.Kata Kunci: Semar, pertunjukan, wayang kulit jawa, gaya Surakarta.